Natural Elements in Malay Proverbs: An Inquisitive Semantic Analysis - Wilda, Dwi Rahma; Hermandra, Hermandra; Sinaga, Mangatur (Jurnal Bahasa dan Sastra, 2024)
A proverb is one of figurative languages delivered from generation to generation aimed to be a guide in living life. Thus, people can learn many lessons through it. In Malay language, there are quite a lot of proverbs that have natural elements such as water, fire, earth, and wind/air in them. Unfortunately, learning about Malay proverbs in schools has not been able to restore the existence of Malay proverbs among young people. This study aims to introduce a different way of studying Malay proverbs, especially those with natural elements, namely by looking for the meaning and reason behind the choice of words in the proverb. By using the method of inquisitive semantics analysis in analyzing the data collected, this study was able to find four elements of nature in Malay proverbs namely the elements of water, fire, earth, and wind/air. Specifically, this study found a total of 8 proverbs with the element of water, 4 proverbs with the element of fire, 4 proverbs with the element of earth, and 4 proverbs with the element of wind/air. This study found the fact that Malay Society is indeed very close to nature as proven by the many natural elements found in Malay proverbs. In these proverbs, many things can be learned, for example, culture, history, and also the mindset of the Malay Society itself.